2016
DOI: 10.1177/0148607115626902
|View full text |Cite
|
Sign up to set email alerts
|

Improved Delivery of Fat From Human Breast Milk via Continuous Tube Feeding

Abstract: Enabling the delivery of the human milk from the top of the feeding bag optimizes fat delivery and limits losses. Such top infusing feeding bags should be developed and could decrease healthcare costs for intestinal rehabilitation programs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…In which their authors speculated was due to the plastic containers causing fat globules to adhere to their surfaces. [24][25] We speculate that our samples did not The second container we tested was silicone.…”
Section: Discussionmentioning
confidence: 97%
“…In which their authors speculated was due to the plastic containers causing fat globules to adhere to their surfaces. [24][25] We speculate that our samples did not The second container we tested was silicone.…”
Section: Discussionmentioning
confidence: 97%
“…A Cochrane review analysis, however demonstrated that both methods are not significantly different in their effects on longterm growth outcomes (13). Other interventions included ultrasonic homogenization of human milk whereby there is less fat separation (14), periodic agitation of the syringe to keep fat suspended (15,16), positioning the syringe vertically with tip upwards to cause fat to float and be delivered earlier in the feeding before it adsorbs to the walls (10,16), moving the tip of the syringe from a central to a peripheral position to leverage the use of the syringe in the horizontal position (17), and using a flat polypropylene plunger head instead of the classical conical rubber head as fat adsorbs more to rubber than polypropylene (17). All of these interventions have been associated with varied degrees of success.…”
Section: Discussionmentioning
confidence: 99%
“…Different strategies to reduce TF-related fat loss have been proposed since the 1980s: motorized feeding bags, 10 roller pumps, 29 top-infusing feeding syringes and bags, 30,31 ultrasonic HM homogenization, 32 fortification of HM with HM-derived fortifiers and cream milk, 33 among others. In this study, we tested 2 different modalities of continuous feeding, which differed between each other only for the position of the syringe tip.…”
Section: Discussionmentioning
confidence: 99%